Analisis Kepecayaan Diri Pada Mahasiswa Unimal - Mulyana Mulyana (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2019)
This study aims to determine student confidence in reality. The research subjects were 93 students consisting of 89 male students and 4 female students. The age range of respondents is 17 to 22 years. Based on psychometric tests conducted through internal consistency and construct validity test, the scale of student self-confidence has less validity and reliability, no validity and no reliability. This measure of self-confidence is due to having Cronbarch's alpha 0.493 while a good measuring instrument must have cronbarch's alpha 0.7 to 0.9. This scale cannot measure the same contract consistently, cannot distinguish individuals with high and low self-esteem, and is invalid for measuring thanksgiving through four factors, namely believing in one's own abilities, acting independently in making decisions, having a positive sense against yourself, and dare to express opinions. With good psychometric standards, the self-confidence scale described and presented in this study cannot be used to measure self-confidence in the context of research and clinical intervention in the student population